Development and feasibility of economical hardware and software in control theory application - Black, Derek J. (Kansas State University, 2017)
Control theory is the study of feedback systems, and a methodology investigated by many engineering students throughout most universities. Because of control theory's broad and interdisciplinary nature, it necessitates further study by application through experimental learning and laboratory practice. Typically, the hardware used to connect the theoretical aspects of controls to the practical can be expensive, big, and time consuming to the students and instructors teaching on the equipment. Alternatively, using cheaper sensors and hardware, such as encoders and motor drivers, can obfuscate the collected data in a way that creates a disconnect between developed theoretical models and actual system results. This disconnect can dissuade the idea that systems can and will follow a modeled behavior. This thesis attempts to assess the feasibility of a piece of laboratory apparatus named the NERMLAB. Multiple experiments will be conducted on the NERMLAB system and compared against time-tested hardware to demonstrate the practicality of the NERMLAB system in control theory application.
Keywords: Control Theory; Software; Higher Education; Motor control; System Identification; Mathematical modeling